The Influence of Kobe Bryant as an Endorser and Subjective Norms on Consumer Purchase Intentions for Nike Basketball Shoes - Henry, Mohammed Alvan Principia; Astuti, Budi; Dharmmesta, Basu Swastha (JDM (Jurnal Dinamika Manajemen), 2023)
Advances in information and communication technology have made it easier for public figures, such as the late Kobe Bryant, a basketball star from the United States, to be recognized by people around the world, including Indonesia. Sportswear and footwear manufacturer Nike has capitalized on its popularity to market sports products, especially basketball shoes, products that fit Kobe Bryant’s area of expertise. This study aims to analyze the effect of attitudes towards Kobe Bryant as an endorser, attitudes towards the Nike brand, and subjective norms on consumer purchase intentions for Nike brand basketball shoes. The population in this study are Indonesian people who have knowledge of Kobe Bryant and the Nike brand but have never bought Nike brand basketball shoes. Primary data was collected by distributing questionnaires boldly to 231 respondents. Purposive sampling tech- nique aims to be used to determine the sample. Four hypotheses have been tested using the AMOS program version 24 and the Structural Equation Modeling (SEM) method, and all hypotheses are supported.